Effectiveness of Salt Hydrolysis Learning Using Diagram I in Guided Inquiry Learning on Student Learning Achievement - Wahid, Fariz Abdul; Mulyani, Sri; Susilowati, Endang (PAEDAGOGIA, 2019)
This study aims to determine the effectiveness of chemistry learning by using Diagram I in guided inquiry learning on student achievement on the subject matter of hydrolysis of salt class XI IPA SMA Negeri 1 Surakarta Academic Year 2017/2018. This research uses experimental method with research design that used is randomized Control group pretest-posttest design. The population used is a class XI IPA SMA Negeri 1 Surakarta The data analysis technique used is by using the right-t test. Based on the results of the study, it can be concluded that learning chemistry using Diagram I in guided inquiry learning on the achievement of learning on the subject of salt hydrolysis is effective to the eleventh grader of SMA Negeri 1 Surakarta in the academic year of 2017/2018. It can be proved by the result of calculation with the value of calculation that is 2.422 higher than the ttable price is 1.671 for the learning achievement of the knowledge aspect, while the Mann-Whitney U test attitude and skill aspects aspects have the significance value of 0.021 and 0.047.